2011
DOI: 10.1097/qad.0b013e32834bba0a
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bacillus Calmette–Guérin cellular immune response in HIV-exposed, uninfected infants

Abstract: BCG-specific T-cell proliferation was reduced in HIV-exposed uninfected infants and IFN-γ concentration was lower in younger exposed infants, showing a delay in immune system maturation of HIV-exposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
1
42
0
1
Order By: Relevance
“…Likewise, assessing T-cell responses to the superantigen SEB, which is used in many assays as a positive control, revealed important attributes of T-cell functionality in these infants. SEB stimulation results in signaling without the need for co-stimulatory molecules, and through multiple Vβ T-cell receptors (TCRS) [46,47]. When polyclonal stimulation with anti-CD3 and anti-CD28 was assessed in other studies, only HEU infants born to mothers with detectable plasma viral loads had increased proliferation compared to their unexposed counterparts [27].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, assessing T-cell responses to the superantigen SEB, which is used in many assays as a positive control, revealed important attributes of T-cell functionality in these infants. SEB stimulation results in signaling without the need for co-stimulatory molecules, and through multiple Vβ T-cell receptors (TCRS) [46,47]. When polyclonal stimulation with anti-CD3 and anti-CD28 was assessed in other studies, only HEU infants born to mothers with detectable plasma viral loads had increased proliferation compared to their unexposed counterparts [27].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these children have been reported to have an increased risk of morbidity and mortality compared with children born to HIV-uninfected mothers [2-6]. This association is thought to be mediated through several factors, including impaired immunity[7-10], premature cessation of breastfeeding [11], and indirect factors such as increased parental mortality, exposure to maternal infections, and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have not observed these differences when infants were BCG vaccinated at birth [13]. These studies were performed in HIV-unexposed populations, and there is evidence that HIV-exposed, uninfected infants may have different Th1 and Th2 cytokine profiles to BCG vaccination [35, 36]. We previously observed that HIV exposure results in reduced breadth and magnitude of cytokine production to BCG and acellular Pertussis vaccination in infants [19].…”
Section: Discussionmentioning
confidence: 99%